Molecular monitoring of Plasmodium falciparum super-resistance to sulfadoxine–pyrimethamine in Tanzania. (December 2016) - Kavishe, Reginald; Kaaya, Robert; Nag, Sidsel; Krogsgaard, Camilla; Notland, Jakob; Kavishe, Adellaida; Ishengoma, Deus; Roper, Cally; Alifrangis, Michael
Abstract Background Sulfadoxine–pyrimethamine (SP) is recommended for prophylactic treatment of malaria in pregnancy while artemisinin combination therapy is the recommended first-line anti-malarial treatment. Selection of SP resistance is ongoing since SP is readily available in health facilities and in private drug shops in sub-Saharan Africa. This study reports on the prevalence and distribution ofPfdhps mutations A540E and A581G in Tanzania. When found together, these mutations confer high-level SP resistance (sometimes referred to as 'super-resistance'), which is associated with loss in protective efficacy of SP-IPTp. Methods DNA samples were extracted from malaria-positive blood samples on filter paper, used malaria rapid diagnostic test strips and whole blood collected from eight sites in seven administrative regions of Tanzania. PCR–RFLP and SSOP-ELISA techniques were used to genotype the A540E and A581GPfdhps . Data were analysed using SPSS version 18 while Chi square and/or Fischer Exact tests were used to compare prevalence between regions. Results A high inter-regional variation ofPfdhps -540E was observed (χ2  = 76.8, p < 0.001). High inter-regional variation of 581G was observed (FE = 85.3, p < 0.001). Both Tanga and Kagera were found to have the highest levels of SP resistance. A high prevalence ofPfdhps -581G was observed in Tanga (56.6 %) in northeastern Tanzania and in Kagera (20.4 %) in northwestern Tanzania and the 540–581 EG haplotype was found at 54.5 and 19.4 %, respectively.Pfdhps -581G was not detected in Pwani and Lindi regions located south of Tanga region. Conclusions Selection of SP super-resistantPfdhps A581G is highest in northern Tanzania. Variation in distribution of SP resistance is observed across the country: northeastern Tanga region and northwestern Kagera region have highest prevalence of SP super-resistance markers, while in Pwani and Lindi in the southeast the prevalence of super-resistance was zero. More studies should be conducted to understand the factors underlying the remarkable heterogeneity in SP resistance in the country.